T009 Animal models of brain stimulation – TMS. Issue 3 (March 2017) - Funke, K.
Abstract : Animal TMS models are especially useful for studying the cellular and molecular effects related to the lasting effects achieved with prolonged stimulation of a particular pattern (rTMS). In translational terms, it is exceptionally challenging to realize stimulation conditions resembling those supposed to occur in the human brain. Due to the very different ratio of coil-to-brain sizes, a focal stimulation of small animal brains as can be achieved in humans using figure-of-eight coils is hardly realistic today. Attempts to develop small (e.g. rodent coils) are confronted with reduced field power or limited number of high-frequency train pulses due to heating problems. Nevertheless, animal TMS models will be helpful in terms of studying relationships between stimulation-induced changes in neuronal activity and plasticity and changes in behavioral phenotypes. Differences in rTMS effects found in Parkinson patients compared to healthy controls which appear to be related to disturbed synaptic plasticity could be replicated in a rat Parkinson disease model (Hsieh et al., 2015 ) and beneficial stimulation effects related to modulation of striatal dopamine content have been reported (Ghiglieri et al., 2012 ). Principally, global brain stimulation using rTMS appears adequate if studying neuromodulatory effects not confined to a particular system as is found with changes in extracellular levels of dopamine or glutamate, brain-derived neurotrophic factor (BDNF), pro- or anti-inflammatory mediators and changes in the excitatory-inhibitory balance (Suppa et al., 2016 ). Nonfocal cortical and/or subcortical stimulation should be suitable to also answer the question if distinct types of neurons (including their genesis and developmental state) or their compartments are more sensitive to a particular stimulation protocol than others if analyzing neuronal activity and plasticity markers. Even if those changes have been achieved with limited focal stimulation in vivo, matched in vitro studies on isolated neuronal systems allow estimating the relevance of focal stimulation as recently demonstrated for the entorhino-hippocampal pathway in mice (Lenz et al., 2016 ). Focal electric stimulation applied in a way to either mimic the timing of spatially distant evoked activity – as in case of interhemispheric stimulation (Barry et al., 2014 )-, or to mimic the electric field distribution likely achieved with an imaginary focal coil could further help to evaluate the differences between focal and global stimulation. However, it has to be kept in mind that magnetic fields induced a different electric field distribution within the tissue as can be achieved with contact electrodes, both with regard to spatial current density and also with regard to extra- and intracellular induction of electric field gradients. In this respect, animal studies demonstrating neuronal effects with patterned magnetic stimulation of rather low field strength (10–100 mT) are of further interest, indicating modulation of molecular processes like intracellular calcium release and gene expression even in the absence of detectable electric responses (Grehl et al., 2015 ). Even if animal models cannot imitate TMS of human cortex in a one-to-one fashion, they definitely offer new ways to investigate how magnetically induced electric field can interact with neuronal processes and which factors determine a variable result of stimulation.